Increase relationship between cadres, party member with people according to the Ho Chi Minh thought - Nguyễn Quang Bình (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The article focuses on clarifying Ho Chi Minh’s thought on the relationship between cadres, party members and the people. Cadres and party members are closely associated with the people which is the socio-political basis, the source of the Party’s strength. On the basis of an overview of Ho Chi Minh’s thought on the relationship between cadres, party members and the people, the author proposes a number of measures to strengthen the relationship between cadres, party members and the people in this period current paragraph.